2019
DOI: 10.1186/s41938-019-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Myco-metabolites as biological control agents against the two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae)

Abstract: Fungi are a promising source for bioactive secondary metabolites against various agricultural pests. Soil samples were collected from the rhizosphere of various plants at El-Khatatba, Egypt, in May 2016. Sixty-two fungal isolates were locally isolated and screened against Tetranychus urticae Koch (Acari: Tetranychidae). Four fungal strains, showed potent control activities, were morphologically identified. Laboratory evaluation of the crude extracts of the selected strains, Aspergillus melleus, A. terreus, Eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Beauvericin showed noticeable acaricidal properties, with LD 50 values from 0.66 to 33 µg/mL, depending on the sensitivity of the T. urticae population to the toxin [ 66 ]. The extract of the soil micromycete Aspergillus melleus , in which mellamide, ochratoxin C, nodulisporic acid, 7-oxocurvularin, and 6-(4′-hydroxy-2′-methyl phenoxy)-(−)-(3R)-mellein were detected, was significantly less toxic to the mites, with an LD 50 of 10 mg/mL [ 67 ]. Thus, TeA demonstrated low activity against sucking insects in the contact intestinal assays.…”
Section: Discussionmentioning
confidence: 99%
“…Beauvericin showed noticeable acaricidal properties, with LD 50 values from 0.66 to 33 µg/mL, depending on the sensitivity of the T. urticae population to the toxin [ 66 ]. The extract of the soil micromycete Aspergillus melleus , in which mellamide, ochratoxin C, nodulisporic acid, 7-oxocurvularin, and 6-(4′-hydroxy-2′-methyl phenoxy)-(−)-(3R)-mellein were detected, was significantly less toxic to the mites, with an LD 50 of 10 mg/mL [ 67 ]. Thus, TeA demonstrated low activity against sucking insects in the contact intestinal assays.…”
Section: Discussionmentioning
confidence: 99%
“…has pathogenic effects on the adult stage of D. gallinae, as a bio-control agent. Mohamed et al 2019 showed that, efficacy of four fungal strains Aspergillus melleus, Aspergillus terreus, Emericella nidulans, and Chaetomium globosum against Tetranychus urticae under Laboratory conditions. Also, observed LC50 values were 10.…”
Section: Acaricidal Activity Of a Aflatoxiformans Against T Urticaementioning
confidence: 99%
“…Beauvericin showed noticeable acaricidal properties with LD50 from 0.66 to 33 µg/mL, depending on the sensitivity of the T. urticae population to the toxin [66]. The extract of the soil micromycete Aspergillus melleus, in which mellamide, ochratoxin C, nodulisporic acid, 7-oxocurvularin, and 6-(4'-hydroxy-2'-methyl phenoxy)-(−)-(3R)-mellein were detected, was significantly less toxic to the mites with LD50 10 mg/L [67]. Thus, TeA demonstrated low activity against sucking insects in the contact-intestinal assays.…”
Section: Entomotoxicity Of Tenuazonic Acidmentioning
confidence: 99%